2013
DOI: 10.1073/pnas.1218806110
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing deformability and surface friction of cancer cells

Abstract: Metastasis requires the penetration of cancer cells through tight spaces, which is mediated by the physical properties of the cells as well as their interactions with the confined environment. Various microfluidic approaches have been devised to mimic traversal in vitro by measuring the time required for cells to pass through a constriction. Although a cell's passage time is expected to depend on its deformability, measurements from existing approaches are confounded by a cell's size and its frictional propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
366
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(393 citation statements)
references
References 42 publications
15
366
3
Order By: Relevance
“…S1E) when cells were in a suspended state, as measured by PMF. Alternatively, it is possible that retention might increase due to cell-surface interactions (Byun et al, 2013), for example if βAR activation changes the surface properties of cancer cells to modulate electrostatic and van der Waals interactions between cells and the porous membrane. However, we determined that there was no significant difference between the adhesion of vehicle-and isoproterenol-treated cells to a silicon nitride atomic force microscope tip (Fig.…”
Section: Results βAr Signaling Reduces the Deformability Of Cancer Cellsmentioning
confidence: 99%
“…S1E) when cells were in a suspended state, as measured by PMF. Alternatively, it is possible that retention might increase due to cell-surface interactions (Byun et al, 2013), for example if βAR activation changes the surface properties of cancer cells to modulate electrostatic and van der Waals interactions between cells and the porous membrane. However, we determined that there was no significant difference between the adhesion of vehicle-and isoproterenol-treated cells to a silicon nitride atomic force microscope tip (Fig.…”
Section: Results βAr Signaling Reduces the Deformability Of Cancer Cellsmentioning
confidence: 99%
“…Our preliminary experiments on MDA-MB-231 cells revealed that cells with reduced expression of lamins A/C were able to pass through the 5µm constrictions significantly faster than comparably sized cells with normal levels of lamins A and C (mock controls). As cell size varied between the various populations and it was recently shown that the transit time of cells through narrow constriction exponentially increases with cell size, 6 we also plotted the regression curves for MDA-MB-231 cells with reduced levels of lamin A/C and mock controls (Fig. 2).…”
Section: Task 1: Acquire a Panel Of Cell Lines And Patient-derived Samentioning
confidence: 99%
“…One approach is the microfluidic cell deformability cytometer which are inexpensive to prototype, use small sample volumes (nanoliters), and employ laminar flow characteristics (24) allowing for predictable and controllable flow. For example, physical constrictions (25)(26)(27)(28) or inertial focusing flow (29)(30)(31) have been used to create contact or shear forces (> 1 nN (30)) capable of significantly deforming flowing cells. Large strains (>10% deformation) however, can damage cells and should be avoided when cell isolation and viability post-analysis are of interest.…”
Section: Introductionmentioning
confidence: 99%